2022
DOI: 10.3390/pathogens11040426
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Coating: Utilisation of Host Serum Sialoglycoproteins by Schistosoma mansoni as a Potential Immune Evasion Mechanism

Abstract: Parasitic helminths resort to various mechanisms to evade and modulate their host’s immune response, several of which have been described for Schistosoma mansoni. We recently reported the presence of sialic acid residues on the surface of adult S. mansoni extracellular vesicles (EVs). We now report that these sialylated molecules are mammalian serum proteins. In addition, our data suggest that most sialylated EV-associated proteins do not elicit a humoral response upon injection into mice, or in sera obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…Helminths, such as S. mansoni , lack the molecular machinery for the biosynthesis of sialylated glycans ( Hokke and van Diepen, 2017 ). Although our data shows that schistosomes in an ex vivo culture do not release EVs with sialylated glycan motifs, it could be possible that host glycoproteins are incorporated into schistosome EVs in vivo, or that host-derived sialic acids get incorporated into schistosome products otherwise ( Dagenais et al, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Helminths, such as S. mansoni , lack the molecular machinery for the biosynthesis of sialylated glycans ( Hokke and van Diepen, 2017 ). Although our data shows that schistosomes in an ex vivo culture do not release EVs with sialylated glycan motifs, it could be possible that host glycoproteins are incorporated into schistosome EVs in vivo, or that host-derived sialic acids get incorporated into schistosome products otherwise ( Dagenais et al, 2022 ).…”
Section: Discussionmentioning
confidence: 76%
“…Frontiers in Molecular Biosciences frontiersin.org in an ex vivo culture do not release EVs with sialylated glycan motifs, it could be possible that host glycoproteins are incorporated into schistosome EVs in vivo, or that hostderived sialic acids get incorporated into schistosome products otherwise (Dagenais et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, perhaps owing to the vastly different properties of the tegument compared to nematode cuticles (a syncytium bounded externally by two lipid bilayer membranes permitting nutrient transport vs a thick acellular barrier that is not actively absorptive (Pappas, 1988;Skelly et al, 1998;Skelly et al, 2014), instances of utilisation of host-derived molecules to avoid immune recognition have largely been described in the context of infection with trematodes, with schistosomes being the most studied. Most of these findings are several years old and have been reviewed recently (Hambrook and Hanington, 2021); however, recent data suggest that schistosomes co-opt yet more host molecules to coat their extracellular vesicles (EVs) (Dagenais et al, 2022).…”
Section: Co-opting Of Host Molecules By Blood-borne Helminthsmentioning
confidence: 99%
“…However, the detection of SA on S. mansoni EVs after an elaborate density-based EV isolation process suggests that SA is associated with EVs rather than simply present in the sample (Dagenais et al, 2021). Mass spectrometry analyses of EV sialoglycoproteins revealed the presence of mammalian serum glycoproteins (Dagenais et al, 2022). It is thus conceivable that schistosomes, and perhaps other helminths, exploit host sialoglycoconjugates, in the form of whole glycoproteins, to aid in the infection process.…”
Section: Co-opting Of Host Molecules By Blood-borne Helminthsmentioning
confidence: 99%
“…The glyco-related molecules on extracellular vesicles (EVs) including exosomes may also affect host cells and environments. Interestingly, S. mansoni EVs contain numerous glycan structures, including sialylated glycoconjugates that seem to be obtained from exogenous sources because the parasite cannot synthesize sialic acids (Dagenais et al, 2022). Kuipers et al showed life stage-specific glycosylation of EVs from S. mansoni and those glycans may have an affect on immune cells through interactions with specific C-type lectins on the host cells, including MGL and DC-Sign.…”
mentioning
confidence: 99%